Enhancing Lecture Interaction through Live SMS - Wilkinson, Robert (HERMES - Journal of Language and Communication in Business, 2010)
A consistent challenge with lectures to large audiences is the extent to which the lecturer can develop interaction with the audience. Obtaining answers to the lecturer’s questions or stimulating questions from the audience during the lecture may be hampered by the fact that the lecturer and the audience are not able to hear speakers in the audience clearly. This article reports on an experimental design to test the feasibility of allowing live SMS messaging as a means to stimulate interaction during large lectures. The context concerned lectures on academic writing in bachelor’s programmes in business and economics. Each lecture attracted about 500 students. The students were invited to send text messages to a dedicated phone line connected to a computer, which, at chosen intervals, displayed messages for everyone to see. The set-up allowed the lecturer to switch instantly from slides to the message display. Messages could be easily transferred to an Excel ﬁ le for subsequent processing if necessary. Results showed that students did not use the opportunity as frequently as expected, and most messages were not relevant to the topics of the lectures. In this article, explanations for these outcomes are discussed, and recommendations for further implementation are presented. Using a new technology, even a pervasive one like SMS messaging, in a lecture entails modiﬁcations to the design, delivery and content of the lecture itself.